RFID security - Thornton, Frank. (Syngress Pub., 2006)
RFID is a method of remotely storing and receiving data using devices called RFID tags. RFID tags can be small adhesive stickers containing antennas that receive and respond to transmissions from RFID transmitters. RFID tags are used to identify and track everything from food, dogs, beer kegs to library books. RFID tags use a standard that has already been hacked by several researchers. RFID Security discusses the motives for someone wanting to hack an RFID system and shows how to protect systems. Coverage includes: security breaches for monetary gain (hacking a shops RFID system would allow a.